Acceso a justicia laboral en Centroamérica - Bolaños, Fernando (Pontificia Universidad Católica del Perú. Fondo Editorial, 2012)
Access to labor justice in Central AmericaThis paper presents a reflection of general character on the most important values and principles that underlie a system of access to the democratic, efficient and fair labor justice. The paper also tries to establish a systematic connection between the concepts of institutionality and access to justice, referring to the interrelationship between both notions and values that feed one another. For work purposes are mentioned and then analyzed four great subthemes: transparency, balance of parties in the labor process, the issue of speedy justice and the principle of effective judicial guardianship. All the above with references to Central America and Dominican Republic legislation and the jurisprudence of the Inter-American Court of Human Rights.

Esta ponencia nos presenta una reflexión de carácter general sobre los valores y principios más importantes que subyacen a un sistema de acceso a la justicia laboral democrático, eficiente y justo. El trabajo pretende además establecer una vinculación sistemática entre los conceptos de institucionalidady de acceso a la justicia, refiriéndose a la interrelación entre ambas nociones y entre los valores que alimentan el uno y el otro. A los propósitos del trabajo se mencionan y analizan entonces cuatro grandes subtemas: la transparencia, el equilibrio de las partes en el proceso laboral, el problema de la justicia pronta, y el principio de tutela judicial efectiva. Todo lo anterior con referencias a la legislación centroamericana y de República Dominicana y la jurisprudencia de la Corte Interamericana de Derechos Humanos.
Keywords: Equilibrio; Celeridad; Concentración; Tutela judicial efectiva; https://purl.org/pe-repo/ocde/ford#5.05.00